Who Should the Child Should Live With? A Student Decision-Making Study Between Brazil and England - Mendes, Josimar Antônio de Alcântara; Ormerod, Thomas; de Almeida, Marília Pacheco; Melo, Giulia Veiga de Leite Ribeiro; Vieira, Luiz Otávio (Estudos e Pesquisas em Psicologia, 2025)
This study aimed to investigate the awareness of undergraduate students regarding the best interests principle of children and adolescents, and how they consider it in cases of custody disputes following conjugal separation. The research employed a quantitative approach with an experimental design based on vignettes. A total of 530 undergraduate students from Law, Psychology, and Social Work programs in Brazil and England were recruited. The results revealed that most students have little knowledge or have never heard of the best interests of the child/adolescent during their academic training. The students tended to maintain the current custody arrangement when dealing with the contextual needs of the child (e.g., mental health, emotional bonds). They changed their decision-making style when dealing with material-physiological needs (e.g., food, housing). This article discusses the implications of these decision-making patterns, as well as the lack of literacy on the best interests of the child/adolescent in the training of these undergraduate students.